Plant Use in the Late Renaissance Gardens of the 17–18th Century Transylvania - Albert Fekete; Máté Sárospataki (Plants, 2023)
The aim of this article is to find, scientifically define, and locate the most frequent occurrences of the gardens of Transylvania in the Late Renaissance period (17–18th centuries), and to collect and prepare a comprehensive plant list of these gardens. During our investigation, based on archival and literary sources, as well as field studies carried out, we identified 81 Late Renaissance residency gardens located in Transylvania. We defined the most typical garden types for the region and we delineated the most characteristic ornamental, fruit, and vegetable plants, including fodder plants, used at that time in residential gardens. Meanwhile, the article intends to give a general overview of the first decisive time period in the Carpathian Basin, represented by the Late Renaissance garden art, from a garden and landscape architectural point of view.